Paclitaxel‐ and sirolimus‐eluting stents in older patients with diabetes mellitus. Issue 7 (26th February 2013) - Buja, Paolo; Facchin, Michela; Musumeci, Giuseppe; Frigo, Anna Chiara; Saia, Francesco; Menozzi, Alberto; Meliga, Emanuele; Sardella, Gennaro; Tamburino, Corrado; Tarantini, Giuseppe
<x xml:space="preserve">Abstract</x> Background Older patients and diabetes mellitus (DM) are rapidly increasing in Western world populations. The treatment of coronary artery disease in these patients is challenging because they are complex and at high risk. Performance of the two widely used drug‐eluting stents (DES), i.e. sirolimus‐ (SES) and paclitaxel‐eluting stent (PES), is understudied in this subset. Aim We aimed to explore the impact of the first generation DES choice on mid term outcome in a large and unselected population of diabetic patients older than 65 years. Methods and Results From a multicenter registry of 2, 429 diabetic patients treated with sirolimus‐ (SES) or paclitaxel‐eluting stent (PES), 1, 417 patients ≥65 years old were analyzed overall and separately for groups aged 65–74 (67%) and ≥75 (33%) years old. SES (55%) were compared to PES (45%) in terms of major adverse cardiac events, including all‐cause death, myocardial infarction (MI) and target lesion revascularization (TLR) throughout 1‐to‐5 year follow‐up (median time 24 months). We failed to find at the unadjusted and adjusted analyses statistically significant differences in term of outcome between the two DES, both in the overall cohort and in the two different aged subgroups, also regardless of the insulin treatment. Conclusions In this real‐life multicenter registry, PES and SES showed a comparable safety and efficacy profile in diabetic patients older than 65 years throughout 1‐to‐5 years follow‐up. © 2012 Wiley Periodicals, Inc.